2019
DOI: 10.7150/ijbs.35356
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a-containing Exosomes Secreted by Irradiated Skin Keratinocytes Delayed the Migration of Unirradiated Skin Fibroblasts

Abstract: Radiation-induced bystander effect (RIBE), e.g. the biological response occurring in unirradiated cells when their neighboring cells are irradiated, is the consequence of intercellular communication between irradiated and unirradiated cells and intracellular signal transduction of these two cell populations. Although several miRNAs have been found to play an important role in RIBEs, the evidence for the regulatory effects of miRNAs on RIBEs is still limited. In this study, by using a two cell-line co-culture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…20 As they can protect the encapsulated molecules from external factors, Exos are ideal nanovesicles for use when delivering miRNAs and other bioactive materials to target cells in an effort to modulate gene expression. 21 Fibroblasts are able to readily internalize serum-derived Exos 22 and are essential mediators of wound healing owing to their ability to promote collagen synthesis and localized remodeling of diverse tissue types. 6 As such, we explored the ability of diabetes patient-derived Exos to alter fibroblast functionality in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…20 As they can protect the encapsulated molecules from external factors, Exos are ideal nanovesicles for use when delivering miRNAs and other bioactive materials to target cells in an effort to modulate gene expression. 21 Fibroblasts are able to readily internalize serum-derived Exos 22 and are essential mediators of wound healing owing to their ability to promote collagen synthesis and localized remodeling of diverse tissue types. 6 As such, we explored the ability of diabetes patient-derived Exos to alter fibroblast functionality in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Research into miR‐27a in fibroblasts has also yielded contradictory results. Experimental data demonstrated that exosome‐derived miR‐27a produced oxidative stress in human skin fibroblasts and inhibited their migration [23] and that miR‐27a overexpression hindered lung fibrosis [45]. In contrast, one report indicated that miR‐27a induced the reprogramming of fibroblasts into CAFs and also promoted proliferation, motility and metastasis of gastric cancer cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…Some of this intercellular crosstalk occurring within the tumour microenvironment is also attributed to exosomes [21]. Exosomes are small membrane vesicles secreted by all types of cells capable of mediating cell‐to‐cell communication by means of exchanging DNA, proteins, mRNAs and miRNAs [22,23]. For instance, in vitro and in vivo models for the human disease have shown that exosome‐derived miR‐27a may regulate the transformation of normal fibroblasts into CAFs and also modulate the growth and metastasis of tumour cells [21].…”
mentioning
confidence: 99%
“…At present, there are not many reports on bystander effects and exosomes produced after high-LET irradiation [ 446 , 447 , 448 ]. Interestingly, Yu et al [ 449 ] and He et al [ 450 ] reported that in exosomes (nanovesicles) derived from the serum of prostate cancer patients after treatment with CIRT (C-ions LET: 33.7 keV/μm), 66 Gy equivalents in daily fractions of 2.75 Gy equivalents) nine specific miRNAs were identified among which expression levels of miR654-3p and miR-378-5p could be correlated with CIRT efficacy and thus could serve as biomarkers for antitumor treatment efficacy [ 449 , 450 ].…”
Section: Ionizing Radiation (Ir) Effects Involving Mitochondriamentioning
confidence: 99%